The masters of private equity and venture capital : management lessons from the pioneers of private investing - Finkel, Robert A.; Greising, David, 1960- (Tantor Media, Inc., 2020)
Ten leading private investors share their secrets to maximum profitability In The Masters of Private Equity and Venture Capital, the pioneers of the industry share the investing and management wisdom they have gained by investing in and transforming their portfolio companies. Based on original interviews conducted by the authors, this book is filled with colorful stories on the subjects that most matter to the high-level investor, such as selecting and working with management, pioneering new markets, adding value through operational improvements, applying private equity principles to non-profits, and much more.